Decolonising the environment through African epistemologies. Descolonización ambiental mediante epistemologías africanas - Woldeyes, Yirga Gelaw; Belachew, Tekletsadik (Universidad Nacional de Colombia, 2021)
This paper examines African epistemologies of the environment as a place-based perspective that regards nature as having its inherent value, personhood, and agency. It presents the African way of relating with or living in the environment as a way of becoming one with nature beyond the discourse of the Anthropocene and environmental change. In particular, we will take African epistemological perspectives from Southern and Eastern Africa, the notions of Ubuntu and Tabot, to reflect on how the environment is traditionally perceived as sacred and part of a living community. The paper also considers how African indigenous ways of knowing and becoming one with nature have been supplanted through epistemic violence, the imposition of western views of the environment over African worldviews through systems and institutions that exclude or exploit local knowledges. Using Ethiopia as a case study, the paper demonstrates how epistemic violence is enacted by excluding indigenous knowledges of the environment from education and disseminating Eurocentric views of the environment. It shall show how the collecting and hording of Ethiopian manuscripts in western institutions has contributed to this loss of indigenous environmental knowledge. Finally, we will examine the importance of African perspectives to decolonise our ways of knowing and relating with the environment, and offer critical insights on how African epistemologies could be used to build a future that is decolonised and sustainable.